2006
DOI: 10.1677/joe.1.06736
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory mechanism by which interleukin-6 stimulates GH-gene expression in rat GH3 cells

Abstract: The present study was performed to elucidate the effect of interleukin (IL)-6 on the human GH (hGH)-gene expression in GH3 rat pituitary tumor cells using stable transfection of the hGH promoter fused to a luciferase reporter gene. Our results showed that IL-6 (10 2 -10 4 U/ml) stimulated GH secretion and synthesis, and promoted the luciferase expression in stably transfected GH3 cells with the maximal action of 1$99 times above the control by 10 4 U/ml IL-6. Among the inhibitors of signaling transduction path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…In this study, the ETEC challenge increased the concentration of IL-6 as previous reported (46,47). High levels of IL-6 reduce the secretion of growth hormone (48) and damage the intestinal epithelium (49,50). The challenge, however, did not affect the concentration of IL-8 and TNFα in this study.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the ETEC challenge increased the concentration of IL-6 as previous reported (46,47). High levels of IL-6 reduce the secretion of growth hormone (48) and damage the intestinal epithelium (49,50). The challenge, however, did not affect the concentration of IL-8 and TNFα in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Stably transfected 3T3-L1 preadipocytes were created as described previously (Gong et al, 2006). In brief, 3T3-L1 preadipocytes (obtained as a generous gift from Department of genetics, Institute of life sciences, Peking University, Beijing, China) were cultured with Dulbecco’s modified Eagle’s-F12 (DMEM/F12, Hyclone, Logan, UT, United States) medium supplemented with 10% FBS, then were plated in 12-well plates at a density of 4.5 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…The construction process was similar to what has been previously described. 19 In brief, total RNA from murine liver of BALB/c mice was extracted using EZNA Total RNA kit (Omega Bio-Tek, Doraville, GA, USA), then reverse transcribed with SuperScript first-strand synthesis system kit (Invitrogen). 2 ml cDNA was amplified with mZAG primers as follows: mZAG forward primer 5 0 -ATGGTGCCTGTCCTGCTGTC-3 0 (20 bp), mZAG reverse primer: 5 0 -TTACTGAGGCTGAGCTACAAC-3 0 (21 bp).…”
Section: Methodsmentioning
confidence: 99%